INOVASI DALAM REKRUTMEN DAN SELEKSI KARYAWAN: STRATEGI MANAJEMEN SUMBER DAYA MANUSIA UNTUK MEMPEROLEH TALENTA UNGGUL - M. Firman S; Nurlelasari Ginting; Jeffry H. Sinaulan; Murthada Murthada; I Made Adi Suwandana (ITB AAS Indonesia Surakarta, 2024)
Superior human resources are very necessary in the current era of globalization. Therefore, it is very necessary for human resources who have superior talent in an organization or company. This aims to provide an understanding related to the innovation process of employee recruitment and selection in order to obtain competent human resources. The method used in this research is a qualitative method with a literature study approach. The results obtained in this research are that in the employee recruitment and selection process an organization can apply things such as being able to to analyze needs, appling competency tests to be a key elemnt in the selection process, conducting an interview process, being a critical stage where companies evaluate, not only technical skill, in the selection process, setting high standart by ensuring that the selection team consists of members perents, further minimizing the risk of value gaps and building trust, conducting reference and background checks on prospective employees, as weel as a trial for 3 months or conducting in-depth interviews. The implication of implementing selection and recruitment is ensuring human resources ar in accordance with the needs and demands of the business environment.